Food supply for nekton in the epipelagic layer of Pacific waters at Kuril Islands in the summer seasons of 2000s - Svetlana V. Naydenko; Alexey A. Khoruzhiy (Известия ТИНРО)
Data of 8 surveys conducted by Pacific Fish. Res. Center (TINRO) in the Pacific waters at Kuril Islands in 2004-2012 are summarized to consider forage base and food relationships of nekton and plankton and to estimate consumption of forage resourced by nekton. The total stock of zooplankton and micronekton in the epipelagic layer changed from 62 to 158 million tons over the shelf and slope of the surveyed area and from 41 to 75 million tons in its deep-water part. Mezopelagic fishes, squids, pacific salmons, and subtropical fishes were the main consumers of these forage resources in summer. The portion of zooplankton stock consumed annually by nekton was relatively low: 4.2-9.3 % for shelf and slope areas (data for 2004, 2007, and 2011) and 4.5-15.6 % for the deep-waters (data for 2004, 2007, 2009, and 2011), without significant year-to-year changes in the diet composition and feeding intensity of nekton. There is concluded that zooplankton and micronekton of the studied area serve successively the food needs of its consumers and carrying capacity of the epipelagic layer in the Pacific waters at Kuril Islands is quite substantial.